Importance of Product Quality, Price, Service and Promotion on Consumer Satisfaction (Case Study of Nasi Bebek Buma Restaurant: Perintis Kemerdekaan Branch) - Friski Okta Ayu Putri; Retnosyari Septiyani; Yunda Maymanah Rahmadewi (Universitas Tanjungpura, 2022)
The importance of food needs causes the food and beverage business never to fade. Implementing a strategy to maintain market shares must be carried out appropriately, especially during the pandemic that caused many companies to go bankrupt. Product quality, price, promotion, and service have direct and significant effects on consumer satisfaction, with case studies on the number of restaurants that went bankrupt due to the pandemic. However, there has been no further research on restaurants that survived this pandemic, such as the Nasi Bebek Buma Restaurant. This study investigated the relationship between product quality, price, promotion, and service on customer satisfaction. This study used a quantitative method with a questionnaire approaching consumers and direct interviews with the owner of the Nasi Bebek Buma Restaurant. This study used a population of consumers of Nasi Bebek Buma Restaurant and a sample of consumers who have bought at Nasi Bebek Buma Restaurant taken by incidental random sampling. Data analysis was obtained using descriptive analysis and classical assumption test using normality test, multicollinearity test, and heteroscedasticity test. In addition, multiple regression analysis was also used to predict the value of the influence of two or more independent variables on the dependent variable to indicate whether there is a functional relationship or causal relationship between two or more independent variables. Hypothesis testing using the F distribution table with a significance level of 5% and a partial regression coefficient significance test (t-test). The results showed that product quality, price, and promotion individually had a positive and significant effect, while service had a positive but not significant effect on consumer satisfaction at Nasi Bebek Buma Restaurant, Perintis Kemerdekaan Branch. The promotion variable is the most dominant variable of consumer satisfaction at Nasi Bebek Buma Restaurant, Perintis Kemerdekaan Branch.